Effects of lifestyle intervention and supplementation with insoluble oat fiber on cognitive functions in patients with prediabetes: a secondary analysis of the Optimal Fiber Trial - Kabisch, Stefan; Montagna, Federico; Honsek, Caroline; Kemper, Margrit; Gerbracht, Christiana; Arafat, Ayman M.; Birkenfeld, Andreas L.; Dambeck, Ulrike; Osterhoff, Martin A.; Weickert, Martin O.; Flöel, Agnes; Pfeiffer, Andreas F. H. (Frontiers in Nutrition, 2026)
BackgroundIn cohort studies, intake of insoluble cereal fiber is associated with multiple health benefits, including preserved cognitive functions. However, evidence from intervention studies is sparse. In the Optimal Fiber Trial (OptiFiT), lifestyle changes and supplementation with oat fiber in prediabetes patients improved glycemic metabolism and body composition, which could be linked to cognitive changes.MethodsIn OptiFiT, 180 patients with impaired glucose tolerance received either an insoluble fiber supplement or a placebo for 2 years in a double-blind, randomized approach, and underwent a parallel 1-year complex lifestyle intervention program. Annual visits included metabolic, anthropometric, and cognitive assessments: Mini-Mental State Examination (MMSE), Verbal Learning Memory Test (VLMT), Regensburg Word Fluency Test (RWFT), Number Connection Test (NCT), Number Recall Test (NRT), and Rey–Osterrieth Complex Figure Test (RCFT). Group-wise comparisons were conducted both globally as well as stratified by age.ResultsCognitive functions only slightly improved—particularly in VLMT and RWFT—without major differences by group or age. At baseline, cognitive function measured by RCFT recall, VLMT, RWFT, and backwards NRT was inversely correlated with age, but not with HbA1c, fasting, or postprandial glucose levels.ConclusionBeneficial effects of insoluble fiber and lifestyle intervention on glycemia might not translate into preserved cognitive capabilities in middle-to-higher aged patients with prediabetes in a 2-year intervention period. Long-term intervention studies in patients with both cognitive vulnerability and metabolic susceptibility are warranted. Such large RCTs should also corroborate putatively involved mechanisms in the epidemiologically assumed protection from cognitive decline.Clinical trial registrationClinicaltrials.gov, identifier NCT 01681173.